Ferromagnetic Sorbents Based on Nickel Nanowires for Efficient Uptake of Mercury from Water - Pinheiro, Paula C.
This work reports the preparation of ferromagnetic nickel nanowires (NiNW) coated with dithiocarbamate-functionalized siliceous shells and its application for the uptake of aqueous Hg(II) ions by magnetic separation. NiNW with an average diameter and length of 35 nm and 5 mu m, respectively, were firstly prepared by Ni electrodeposition in an anodic aluminum oxide template. The NiNW surfaces were then coated with siliceous shells containing dithiocarbamate groups via a one-step procedure consisting in the alkaline hydrolytic co-condensation of tetraethoxysilane (TEOS) and a siloxydithio-carbamate precursor (SiDTC). A small amount of these new nanoadsorbents (2.5 mg.L-1) removed 99.8% of mercury ions from aqueous solutions with concentration 50 mu g.L-1 and in less than 24 h of contact time. This outstanding removal ability is attributed to the high affinity of the sulfur donor ligands to Hg(II) species combined with the high surface area-to-volume ratio of the NiNW.